The Survey of Students’ Opinion on the Integration of Physical Activity in General Education Subjects: A Case Study of Bangkokthonburi University - Siriphan, Chanchai; Saksanit, Watchira; Ragyoo, Somsak; Saraphak, Nitiphan; Kruatiwa, Chareon (Interdisciplinary Academic and Research Journal, 2023)
Physical activity or physical activity is caused by the work of the skeletal muscles, in which physical movement causes the body to use more energy from normal conditions. If the body moves regularly, it will be a behavior that helps promote complete health and can reduce the risk of various diseases. Thus, the objective of this research was to study the level of students’ opinions in years 1-4. To integrate physical activity in general education subjects. The population and sample were students of Bangkokthonburi University. Registered for the first semester of the academic year 2022, a total of 400 students accidental sampling. The instrument used for data collection was a questionnaire on the opinions of Bangkokthonburi University students about the integration of physical activity in general education subjects created by the researcher The confidence value was .92. The data were analyzed by frequency distribution, percentage, mean, standard deviation. The results showed that: 1. The students’ opinions about attitudes toward exercise were at a high average level. Because most students have direct experience with the benefits of exercise. Therefore, the value and have a good attitude 2. The students’ opinions about exercise behavior were at a high average level. Because when students have a good attitude about exercising, students have good behaviors in exercising for health. because attitudes are related to behavior 3. The students’ opinions about the integration of physical activity in general education subjects were at a high level. Because students see that sitting in the study for a long time without relaxation, changing the position may have negative effects on health in the future.